Comparison of Outcomes of Pneumatic Ballistic Lithotripsy, Holmium Laser Lithotripsy, and Combined Electromagnetic with Ultrasonic Lithotripsy during Percutaneous Nephrolithotomy - Ejaz, Mansoor; Saulat, Sherjeel; Qadri, Syed Saeed Uddin; Ayub, Awais (Pakistan Armed Forces Medical Journal, 2023)
Objective: To compare outcomes of combined electromagnetic with ultrasonic lithotripter, pneumatic ballistic lithotripter, and holmium laser lithotripter among patients at a Tertiary Care Hospital.Study Design: Prospective comparartieve study.Place and Duration of Study: Department of Urology at Tabba Kidney Institute, Karachi Pakistan, from May 2020 to Jun 2021.Methodology: Ninety patients were divided into three groups of lithotripsy energies. Group-A (n=30) patients got pneumatic lithotripsy, Group-B (n=30) patients got laser lithotripsy, while Group-C (n=30) patients got trilogy lithotripsy technique. Outcomes such as post-operative pain, post-operative complications, and stone clearance were evaluated in all groups.Results: The overall mean age of the patients was 50.23±9.24 years, ranging from 33-74 years. The majority of the participants were males (n=52,57.8%), and 38(35.6%) of the participants were females. The intra-operative time, severity of post-operative pain, fever and UTI were the same between the three groups. However, the proportion of hematuria (p=0.001) and stone clearance (p=0.025) significantly differed between the three groups.Conclusion: Laser and pneumatic lithotripter were more effective in complete stone clearance than trilogy lithotripter. While laser lithotripter significantly decreases the occurrence of hematuria.